2014
DOI: 10.1155/2014/863984
|View full text |Cite
|
Sign up to set email alerts
|

The Galloyl Catechins Contributing to Main Antioxidant Capacity of Tea Made fromCamellia sinensisin China

Abstract: Total polyphenol content, catechins content, and antioxidant capacities of green, dark, oolong, and black teas made from Camellia sinensis in China were evaluated. The total polyphenol content of 20 samples of tea was in the range of 7.82–32.36%. Total catechins content was in the range of 4.34–24.27%. The antioxidant capacity of tea extract was determined by the oxygen radical absorbance capacity (ORAC) test and the 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging test. Total polyphenol content, catech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 31 publications
(29 reference statements)
3
35
3
Order By: Relevance
“…3,4 Numerous studies have reported that drinking tea imparts various physiological and pharmacological benets which include, anti-diabetic, anti-inammatory, antioxidant, anticholesterolemic, anti-mutagenic and anticarcinogenic activities. [5][6][7][8][9][10] Jin Guanyin, also known as the no. 1 of Mingke tea (a new variety of tea that cultivated by the Tea Research Institute of Fujian Academy of Agricultural Sciences), is a new breed of clones that adopted the hybrid breeding method with the Tie Guanyin as the female parent and the golden GUI as the male from 1978 to 1999.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Numerous studies have reported that drinking tea imparts various physiological and pharmacological benets which include, anti-diabetic, anti-inammatory, antioxidant, anticholesterolemic, anti-mutagenic and anticarcinogenic activities. [5][6][7][8][9][10] Jin Guanyin, also known as the no. 1 of Mingke tea (a new variety of tea that cultivated by the Tea Research Institute of Fujian Academy of Agricultural Sciences), is a new breed of clones that adopted the hybrid breeding method with the Tie Guanyin as the female parent and the golden GUI as the male from 1978 to 1999.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies also reported that TPC and TFC are higher in GT than BT (Quan et al ., ; Taheri et al ., ; Carloni et al ., ; Pavlović et al ., ; Zielinski et al ., ). It was also reported that green tea contains more TPC than oolong tea followed by black tea (Zhao et al ., ). The difference in TPC is due to the variation in the manufacturing methods used to obtain different tea types (Quan et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Although the antioxidant potential of theaflavin 3,3‐gallate is more than EGCG found in green tea, the amount is much lesser due to which black tea is less effective in scavenging radicals (Chan et al ., ). The present study is in agreement with the previous findings demonstrated similar outcomes where green tea scavenging potential was stronger than the oolong and black teas (Carloni et al ., ; Zhao et al ., ; Nadiah et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…Tea catechins are well known as powerful antioxidants and they have been studied as coronary artery disease (CAD) and cancer chemopreventative agents (Deka & Vita, 2011;Kuriyama et al, 2006;Zheng et al, 2011). Health benefits including the reduced risk of CAD by consumption of green tea are attributed to the antioxidant characteristics of the catechins (Rietveld & Wiseman, 2003;Zhao, Li, Liu, & Yang, 2014). Important catechins in green tea include (+)-catechin (C), (-)-epicatechin gallate (ECG), (-)-epigallocatechin (EGC), (-)-epigallocatechin gallate (EGCG), (-)-gallocatechin (GC), and JFDS-2017-1898Submitted 11/20/2017, Accepted 2/23/2018 (-)-gallocatechin gallate (GCG).…”
Section: Introductionmentioning
confidence: 99%